Biochemical, Anatomical, and Pharmacological Characterization of Calcitonin-Type Neuropeptides in Starfish: Discovery of an Ancient Role as Muscle Relaxants - Cai, Weigang; Kim, Chan-Hee; Go, Hye-Jin; Egertová, Michaela; Zampronio, Cleidiane G.; Jones, Alexandra M.; Park, Nam Gyu; Elphick, Maurice R. (Frontiers in Neuroscience, 2018)
Calcitonin (CT) is a peptide hormone released by the thyroid gland that regulates blood Ca2+ levels in mammals. The CT gene is alternatively spliced, with one transcript encoding CT and another transcript encoding the CT-like neuropeptide calcitonin-gene related peptide (α-CGRP), which is a powerful vasodilator. Other CT-related peptides in vertebrates include adrenomedullin, amylin and intermedin, which also act as smooth muscle relaxants. The evolutionary origin of CT-type peptides has been traced to the bilaterian common ancestor of protostomes and deuterostomes and a CT-like peptide (DH31) has been identified as a diuretic hormone in some insect species. However, little is known about the physiological roles of CT-type peptides in other invertebrates. Here we characterized a CT-type neuropeptide in a deuterostomian invertebrate – the starfish Asterias rubens (Phylum Echinodermata). A CT-type precursor cDNA (ArCTP) was sequenced and the predicted structure of the peptide (ArCT) derived from ArCTP was confirmed using mass spectrometry. The distribution of ArCTP mRNA and the ArCT peptide was investigated using in situ hybridization and immunohistochemistry, respectively, revealing stained cells/processes in the nervous system, digestive system and muscular organs, including the apical muscle and tube feet. Investigation of the effects of synthetic ArCT on in vitro preparations of the apical muscle and tube feet revealed that it acts as a relaxant, causing dose-dependent reversal of acetylcholine-induced contraction. Furthermore, a muscle relaxant present in whole-animal extracts of another starfish species, Patiria pectinifera, was identified as an ortholog of ArCT and named PpCT. Consistent with the expression pattern of ArCTP in A. rubens, RT-qPCR revealed that in P. pectinifera the PpCT precursor transcript is more abundant in the radial nerve cords than in other tissues/organs analyzed. In conclusion, our findings indicate that the physiological action of CT-related peptides as muscle relaxants in vertebrates may reflect an evolutionarily ancient role of CT-type neuropeptides that can be traced back to the common ancestor of deuterostomes.